Managed Labor Migration in Afghanistan : Experience and Evidence with International Afghan Labor Mobility at Macro Level - Garrote Sanchez, Daniel (World Bank, Washington, DC, 2018)
Migration in Afghanistan has been a relevant phenomenon during the last several decades, driven by a complex combination of protracted conflict, food insecurity, natural disasters, and socioeconomic factors. Around 4.8 million Afghan currently live abroad, most of them in neighboring Iran and Pakistan. While prior migration waves consisted of refugees to a large extent, in the last decade economic migrants have been increasingly prevalent, not only to Iran but also to Gulf Cooperation Council and Organisation for Economic Co-operation and Development countries. Due to the lack of formal mechanisms for migration, however, the vast majority of flows have an irregular nature. As a consequence, official statistics vastly underestimate the value of remittances at 1.7 percent of GDP, while analysis that includes informal channels raise this figure by up to 10 times. Overall, although a relatively small share of families benefits from remittances, they provide a vital source of income and act as a buffer against income shocks.